THE EFFECT OF PROBLEM POSING LEARNING MODEL ON STUDENT LEARNING OUTCOMES AT SMA NEGERI 19 MEDAN - muhammad ali hamzahas (UNIVERSITAS NEGERI MEDAN, 2023)
This study aims to determine the effect of the problem posing learning model on high school students' physics learning outcomes. This research is a type of quasi-experimental research with a two-group pretest and posttest design. The population of this study consisted of 10 classes and the sample was taken by means of cluster random sampling. Class XI-1A as the experimental class and class XI-1B as the control class, each of which has 30 students. The instrument used in this study was a test of learning outcomes in the form of multiple choice of 20 questions and student activities using observation sheets. Data analysis was performed by t test. The results showed that the average pre-test and post-test values in the experimental class were 54.83 and 75.33, respectively, while the average pre-test and post-test scores in the control class were 53.83 and 64.33, respectively. The activity of students in the experimental class increased at each meeting by 60.33 (active enough) at the first meeting, the second meeting was 67 (active enough) and the third meeting was 70.33 (active) with an average of 65.88 in the moderately active category. Data analysis using the t test concluded that there was an influence of the problem posing learning model on high school students' physics learning outcomes.